Knowledge Dilution, Pollution, and Burden in Digital Media - Sridhar, M. S. (Journal of Information and Knowledge, 2024)
Knowledge, having glorified as biggest power of present day, has too much repetition, fake/false information and growing at a fast rate with unedited and unchecked for quality of data and information on digital media. The result is obvious dilution and pollution of knowledge. Unchecked growth of the wrong kind also led to knowledge burden. Such knowledge burden cause decidophobia instead of knowledge aiding decision making. General decline in proportion of disruptive research also led to enormous increase of repetitive growth of knowledge. How libraries can overcome these problems in their information services is the biggest challenge of the time.